2007
DOI: 10.1016/j.neulet.2007.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Ku70 subunit (XRCC6) and protection from low dose ionizing radiation during zebrafish embryogenesis

Abstract: The Ku70 protein, a product of the XRCC6 gene, is a component of the nonhomologous end-joining (NHEJ) pathway of DNA repair, which protects cells from the effects of radiation-induced DNA damage. Although the spatial expression of Ku70 during vertebrate embryogenesis has not been described, DNA repair proteins are generally considered to be "housekeeping" genes, which are required for radioprotection in all cells. Here, we report the cloning and characterization of the zebrafish Ku70 ortholog. In situ hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…This repair pathway is conserved within vertebrates. Putative orthologs for each of these were identified in the zebrafish (Danio rerio) EST database and studied [5,6]. The presence of these genes, together with the functional characterization of the Ku70 and Ku80 genes in the zebrafish, suggest that an intact functional NHEJ probably operates in the zebrafish and also in other fish species.…”
Section: Introductionmentioning
confidence: 99%
“…This repair pathway is conserved within vertebrates. Putative orthologs for each of these were identified in the zebrafish (Danio rerio) EST database and studied [5,6]. The presence of these genes, together with the functional characterization of the Ku70 and Ku80 genes in the zebrafish, suggest that an intact functional NHEJ probably operates in the zebrafish and also in other fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al revealed that the p53 protein in mutant p53 zebrafish embryos upon ionizing radiation exposure maintained a very high level when compared to wild-type embryos, thereby suggesting that the p53 protein played a crucial role in IR-induced carcinogenesis [57]. Bladen et al suggested that Ku70 and Ku80 were essential in repairing IR-induced DNA damages in zebrafish embryos through the nonhomologous end-joining (NHEJ) pathway [58,59]. Jaafar et al studied the long-term effects of Îł-rays in adult zebrafish and in zebrafish embryos in terms of gene expression in the liver tissue using Affymetrix microarray [60], and found that more than 300 transcripts were modified in the liver of adult zebrafish liver upon Îł-irradiation with doses of 0.1 and 1.0 Gy [60].…”
Section: Ionizing Radiation Targeted Effects and Non-targeted Effmentioning
confidence: 99%
“…Renal function and neurotoxicity have also been employed [32] but these are only suitable for examining the radiation effects to specific organs. To investigate the effect of radiation on the whole embryos, quantification of the apoptotic signals is widely used [28,30,33,34].…”
Section: Biological Endpoint For Quantification Of Adaptive Responsementioning
confidence: 99%